FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS BATANG III - Imam Purnomo; Zaenal Amirudin; Supriyo . (LPPM Universitas Pekalongan, 2014)
Patient satisfaction is a person's level of perceived circumstances that are the result of comparing the performance or outcome of product perceived in relation to one's expectations. Stem health center III is one of the health service which is visited by patients. Based on data from patient visits in the last 3 months (January-March 2013) also found a decrease in the number of visits or tend to be unstable. That was in January, as many as 229 patients, more than 254 patients in February and March, as many as 171 patients. With the picture of the researcher interested in taking a research on the factors - factors related to outpatient satisfaction in Batang health center III. This study used a descriptive cross sectional analytic approach to the interview using a questionnaire. Based on the survey results revealed There is a relationship between Reliability, Responsiveness, Empaty, Assurance, Tangible, perceived benefits, perceived barriers to outpatient satisfaction in Batang health center III. Suggestions in this research is expected that officers should be more concerned about the patient's health and help trouble when patients need information about health center III Rod and provide packets of information, including cost information packet, when it comes to Batang health center patients III should immediately give a greeting or welcome and officers provide information to customers carefully and answer clearly any complaints, criticisms and suggestions from patients, health centers intensify Batang health center III so that for patients who are far away from the Batang health center III does not need to be expensive for reaching health centers. Keywords: Satisfaction, Patient of Batang Health Center III